SELF INCOMPATIBILITY MECHANISMS IN THE CROCUS SATIVUS AGGREGATE (IRIDACEAE): A PRELIMINARY INVESTIGATION - ZANIER, R.; GRILLI CAIOLA, M. (Annali di Botanica, 2000)
Two molecular mechanisms responsible for SI (Self-Incompatibility) in dicotyledons were tested in the C. sativus L. aggregate. RNase and peroxidase activity assays were carried out on crude extract from un-, self- and cross-pollinated styles of C. sativus (male-sterile), C. thomasii Ten. (outfertile) and C. cartwrightianus Herb (out-fertile). Results on RNase activity indicate that in the Crocus species studied the rejection mechanism of SI is not based on stylar RNase. Data on peroxidase activity indicate a relationship between pollen tube presence in the style and stylar peroxidase activity. Stylar peroxidase activity increase is related to pollen tube presence but does not stop tube growth. Compatible and incompatible pollen tubes grow along the style and their discrimination occurs in another region of the gynoecium.